Evaluation of efficacy and safety of oral olmesartan + chlorthalidone combination in the management of hypertension in Indian patients - Bramhabhatt, Vijay; Jha, Manoj Kumar; Faruqui, Arif A. (International Journal of Research in Medical Sciences, 2017)
Background: Hypertension is a major health problem in India. Being a multifactorial condition often requires the administration of multiple drugs. Despite improvements in the management of hypertension and the availability of effective antihypertensive agents, only 50% of these individuals achieve BP control. The present study was undertaken to evaluate the efficacy and safety of, fixed dose combination of olmesartan 40 mg + chlorthalidone 12.5 mg, in the management of hypertension uncontrolled with olmesartan monotherapy. Methods: 110 patients were enrolled in this Post-Marketing Surveillance (PMS) study. Patients were prescribed to take fixed dose combination for 60 days. Results: There was significant decrease (P <0.0001) in Systolic Blood Pressure (SBP) & Diastolic Blood Pressure (DBP) from the baseline to 15th, 30th and 60th days of the treatment. At the end of the study period of 60 days 95.4% & 90.9% patients of age group >60 years and <60 years achieved the Joint National Committee (JNC VIII) recommended goal respectively. (<150/90 for elder patients aged above 60 year and 140/90 for those aged less than 60 years). Conclusion: Thus fixed dose combination therapy of olmesartan & chlorthalidone has been shown to be excellent in efficacy and tolerability & gives another option for the optimal management of hypertension.